Synthesis, Characterization and Kinetic Studies of Chelate Polymer Derived from 3-Nonyl Benzene and its Use for the Removal of Some Heavy Metals from Aqueous Solutions - Khalaf, Qadoori Zidan; Al-Jubori, Hamid Mohammed Saleh; Al-salihi, Kareem Jumaah (Iraqi Journal of Science, 2021)
A new chelate polymer (2-5-hydroxy-3-methyl-2- (3-nonyl benzene) imino) methyl) benzyl) 4-6-dimethyphenol] (K4) was prepared by using the condensation reaction method and identified by several techniques, including FT-IR, NMR, and atomic absorption spectroscopy, as well as TG-DTA thermal analysis. The kinetic equilibrium for the sorption of lead and cadmium ions on the chelate polymer surface was also investigated. The results showed that the sorption of both ions followed the pseudo-first-order and pseudo-second-order kinetic equilibrium. The rate constant values of pseudo-first-order reaction were equal to 0.062 and 0.057 min-1 , while the values of pseudo-second-order were 0.0103 and 0.053 L.mg-1 min-1) for the sorption of Pb (II) and Cd (II) on chelate polymer, respectively. Thermodynamic parameters were also investigated and the sorption values for Pb+2 were achieved at 25 oC, ΔG = 0.436 KJ/mole, ΔH = 10.55 KJ/mole, and ΔS= 0.08 KJ/mole, , whereas those for Cd+2 were 25 oC , ΔG = -2.345 KJ/mole, ΔH = 4.378 KJ/mole, and ΔS= 0.09 KJ/mole. The results showed that the sorption process was spontaneous and endothermic in nature for the sorption of each of Pb+2 and Cd+2 on polymer surface.